FACTORS AFFECTING CAREER SELECTION OF ACCOUNTING STUDENTS TO BECOME PUBLIC ACCOUNTANTS - Supriyadi, Stevanus Gatot; Jatmika, Dodik; Asnawi, Asnawi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
The purpose of this reseasrch was to know what factors influence accounting students in choosing a career to become a public accountant. Factors that influence career choice to become a Public Accountant are assessed by variables of reward/salary, professional training, professional recognition, social values, work environment, labor market considerations, and personality. Data collection was carried out by distributing questionnaires to accounting students at Universitan Pawyatan Daha Kediri. The sample used was 90 respondents. Data analysis in this study used multiple regression analysis with the help of SPSS version 23.00. The results of this analysis indicate that simultaneously the factors of reward, professional training, professional recognition, social values, work environment, labor market considerations and personality have a significant influence on career choice to become a public accountant. Partially, professional recognition, labor market considerations and personality have a significant influence on career choice to become a public accountant, financial rewards, professional training, social values and work environment do not have a significant effect on career choice to become a public accountant. Keywords: financial/salary award, professional recognition, social values, work environment, personality and career choice